Strategic choice of stock pollution: Why conservatives (appear to) turn green - Achim Voß (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2014)
The public management of stock pollutants is an intertemporal problem; today's optimal choice takes the behavior of future governments into account. If a government expects a successor with different environmental preferences - for instance, if Conservatives expect green successors - it must choose strategically. I model this interaction in a two-period game in which the government of each period chooses consumption as a flow variable that adds to a stock of pollution. In this setting, I analyze how the prospect of losing political power changes the incumbent's policy choice. It is shown that both the prospect of a more conservative or of a greener successor reduce present consumption. This implies that losing power in the future makes a conservative government choose a compromise policy today - which may explain why in some countries, conservative governments seem to adopt green policies. By contrast, the expected loss of power makes a green government choose a policy that appears as a radicalization of their position.
Keywords: Q58; D72; C72; 330; Stock Pollution; Political Economy of Environmental Policy; Time Inconsistency; Strategic choice of stock variables; Sequential Game; Partisan Politicians; Ideological Preferences; Green Parties